PERHITUNGAN WETON PERKAWINAN MENURUT ADAT JAWA: Perspektif Kitab Al-Fara`Id Al-Bahiyyah - Nur Qomari (Malang Prodi. Ahwal Al-Syakhsiyyah, IAI Al-Qolam, 2023)
Marriage is a religious ritual in Islam that was also followed by the Prophet Muhammad. Almost all ethnicities have different customs. One of the Javanese customs in conducting a wedding is by calculating the weton or day of birth. The weton determines a prediction about the future fate of the family. The purpose of this research is to find out how the connection between the weton tradition that takes place before the wedding with the perspective of one of the books of fiqh rules, namely the book of al-Faraid al-Bahiyyah. This research method is a library research genre using a content analysis approach. The findings of this study include: a) In the implementation of the weton tradition, the Javanese community is divided into two groups, firstly kejawen, a group that makes weton as a benchmark for marriage and believes in it. The second is potehan, a group that is afraid of polytheism. They do not use weton completely. b) Weton according to the book al-Faraid al-Bahiyyah has fulfilled the requirements of custom and can be used as a basis for law, the conditions are first, custom can be used as a basis for law if it is muththarid (applies evenly) in an area. Secondly, if there is a conflict between `urf jali and shara' then the former takes precedence, if it is not related to the law of shara'. Third, `Urf khash if it is not limited to a particular area, then it can be used as a legal basis.Fourth, the standard of `urf that can be used as a landmark